2005
DOI: 10.1111/j.1362-1017.2005.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of patient diaries in an intensive care unit

Abstract: Many patients experience posttraumatic stress disorder following a stay in intensive care; this can be due to a lack of recall of their stay. Retrospective patient diaries (n = 8) with follow-up have been used to try and help patients' recovery but have been found to be impersonal. Prospective diaries (n= 35) were implemented and trialled with follow-up at 2, 6 and 12 months postdischarge. Patients' and relatives' initial feedback regarding diaries is extremely positive. Benefits included better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 8 publications
1
113
0
3
Order By: Relevance
“…This is in accordance with the majority of reported patient diary usage which has been within Europe, particularly Scandinavia [18][19][20]51] and the United Kingdom [22,52].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with the majority of reported patient diary usage which has been within Europe, particularly Scandinavia [18][19][20]51] and the United Kingdom [22,52].…”
Section: Discussionsupporting
confidence: 90%
“…Observational [22,38,[40][41][42][43], prospective cohort with a retrospective reference group [39] , timeseries [1] and qualitative [52,[54][55][56][57] studies have reported the success and importance of patient diaries in the clinical setting. Our review has demonstrated the paucity of randomized controlled trials evaluating patient diaries.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evaluations and reports on patient diary use with ICU patients suggested that they assisted patients in accepting the severity of their illness and helped relatives cope with feelings of grief and loss, with subsequent studies reporting that diaries improved communication channels. 6,13,14 These descriptive studies served to explore patients' and families' views of diary use, their content and processes, which generally indicated a positive reception, and laid the foundation for subsequent studies. 6,13,14 There have only been three trials that have examined the impact of diaries on patient and family psychological outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent randomized controlled trial demonstrated a significant reduction in the incidence of PTSD when patient diaries are used (5% vs. 13%, p=0.02) [2]. Patient diaries are currently used in many UK ICUs and other European countries to reduce PTSD and improve patient rehabilitation [11,12].…”
Section: Introductionmentioning
confidence: 99%